CARDIOPROTECTIVE ACTIVITY OF LEAVES OF KIGELIA AFRICANA ON ISOPRENALINE INDUCED MYOCARDIAL INFARCTION - Yalu, Honi; P. K. M, Nagarathna; Ranjan mondal, Lokesh (International Journal of Ayurveda and Pharma Research, 2015)
Kigelia Africana is an herbal medicinal plant and it is used to cure different disorders. The present study was involved in cardioprotective activity of leaves of Kigelia Africana on ISO induced myocardial injury. Male wistar rats are divided into five groups of six animals each. All the grouped rats were pre-treated with the extract and standard (propranolol 10 mg/kg) either s.c. or orally for eight days. Then, they were given 5.25 and 8.5 mg/kg isopreterenol s.c. on two consecutive days. Early treatment with extract of Kigelia Africana 100mg/kg, 200 mg/kg showed significant decrease in level of serum marker enzymes aspartate transaminase (AST), lactate dehydrogenase (LDH), alanine transaminase (ALT), alkaline phosphatase (ALP), changes in the oxidative stress markers like lipid peroxidase (LPO), glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) caused by ISO (5.25 and 8.5 mg/kg). The defence action of leaves of Kigelia Africana concluded by observing histopathology and are more consistent at 200mg/kg. Hence, we conclude that pre-treatment with extract of leaves of Kigelia Africana more barrier aganist the ISO induced myocardial injury.